Making accountable teachers: the terrors and pleasures of performativity - Holloway, Jessica; Brass, Jory (Journal of education policy, 2018)
This article draws from Stephen Ball's work on markets, managerialism, and performativity to frame a comparative study that examines the reconstitution of the teacher-subject across a pivotal decade in which neoliberal standards and accountability reforms effected significant changes in US education. It juxtaposes two qualitative studies conducted during the implementation of successive standards and accountability movements. The first study of early career English teachers coincided with the implementation of the Bush administration's No Child Left Behind Act of 2001 (NCLB), and the second took place nearly a decade later as states began to implement value-added teacher assessments in conjunction with the Obama administration's Race to the Top (RTTT). The juxtaposition of these two studies points to a paradigmatic shift in the construction of teachers' professional knowledge and subjectivity. While teachers of the first accountability stage positioned NCLB's (self-) disciplinary mechanisms as external intrusions on their autonomy, professionalism, and practice, the second group positioned RTTT's accountability mechanisms as the very modes by which they knew themselves and their quality. Thus, these studies show a collapse between the governed (i.e. teachers) and the government (i.e. accountability mechanisms) and the normalization of the marketized teacher, the managed teacher, and the performative teacher.